1990
DOI: 10.1088/0952-4746/10/2/005
|View full text |Cite
|
Sign up to set email alerts
|

A survey of habits of people living close to the Sellafield nuclear processing plant

Abstract: A survey has been carried out of the habits of people living within 3 km of the Sellafield nuclear reprocessing plant. The survey included estimates of consumption rates of foodstuffs for a range of ages and of time spent indoors, outdoors and away from home. A high proportion of those interviewed were farmers and they provided additional data on time spent in the various farming activities. A comparison of the food consumption rates and generalised values recommended for critical groups by the NRPB and MAFF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Most of the local farmland is pasture for sheep and cattle. Though this might suggest that there is little risk of any alpha-emitting radioactive particles being consumed directly by humans, a habit survey of the local population (Stewart et al 1990) found that, for more than half the sample group, the majority of vegetables consumed were home grown. Thus the consumption of home-grown vegetables may provide a route into the human food chain for radioactive particles.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the local farmland is pasture for sheep and cattle. Though this might suggest that there is little risk of any alpha-emitting radioactive particles being consumed directly by humans, a habit survey of the local population (Stewart et al 1990) found that, for more than half the sample group, the majority of vegetables consumed were home grown. Thus the consumption of home-grown vegetables may provide a route into the human food chain for radioactive particles.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the food products consumed by residents of Cumbria are assumed to be produced outside of the region, as the majority of people in the UK obtain their groceries from supermarkets, who source their products very widely. However, 25% of people were assumed to grow some of their own fruit and vegetables (Stewart et al, 1990), but, on average, this only constituted 10% of their total intake of this food group. For the other food product groups, the majority of the produce consumed was assumed to be derived from outside of the region, with small fractions being sourced from within the region.…”
Section: Data Sources For Cumbrian Scenariomentioning
confidence: 99%
“…Une étude de budget temps réalisée sur les populations proches du site de Sellafield (Stewart et al, 1990) indique que les agriculteurs constituent le groupe de population passant le plus de temps à l'extérieur avec 30 % du temps passé à l'extérieur. Cependant, la valeur préconisée par le NRPB pour les travailleurs qui ne sont pas dans un bureau ou un autre local est 50 % du temps passé à l'extérieur.…”
Section: Comportements Particuliersunclassified
“…De même, l'étude Suisse (Stewart et al, 1990) utilise un facteur de protection par rapport au dépôt extérieur de 0,l.…”
Section: Irradiation Externe Par Le Dépôt Sur Le Soiunclassified